Sauroxine reduces memory retention in rats and impairs hippocampal long-term potentiation generation - Vallejo, Mariana Guadalupe (2017)
In the present paper it was investigated the role of sauroxine, an alkaloid of Phlegmariurus saururus, as a modulator of some types of learning and memory, considering the potential nootropic properties previously reported for the alkaloid extract and the main alkaloid sauroine. Sauroxine was isolated by means of an alkaline extraction, purified by several chromatographic techniques, and assayed in electrophysiological experiments on rat hippocampus slices, tending towards the elicitation of the long-term potentiation (LTP) phenomena. It was also studied the effects of intrahippocampal administration of sauroxine on memory retention in vivo using a Step-down test. Being the bio distribution of a drug an important parameter to be considered, the concentration of sauroxine in rat brain was determined by GLC–MS. Sauroxine blocked LTP generation at both doses used, 3.65 and 3.610−2 μM. In the behavioral test, the animals injected with this alkaloid (3.65 10−3 nmol) exhibited a significant decrease on memory retention compared with control animals. It was also showed that sauroxine reached the brain (3.435 μg/g tissue), after an intraperitoneal injection, displaying its ability to cross the blood-brain barrier. Thus, sauroxine demonstrated to exert an inhibition on these mnemonic phenomena. The effect here established for 1 is defeated by other constituents according to the excellent results obtained for P. saururus alkaloid extract as well as for the isolated alkaloid sauroine.